THE ALBUM IN THE TEACHING-LEARNING PROCESS OF INVERTEBRATE ZOOLOGY - Armiñana-García, Rafael (2022)
The objective of the research work was to propose a teaching method that allowed the self-management of knowledge related to the zoology of invertebrates by the students of the 3rd year of the Bachelor of Education career, comparing in-person learning vs. those not in attendance. For the development of the research, information gathering and processing methods were used, which allowed us to verify the shortcomings in terms of the use and elaboration of this type of teaching medium, for the teaching-learning process from the non-face-to-face modality. The illustrations were made to correspond with the pedagogical and hygienic requirements, which contributed to the aesthetic education of the students and raised the interest in the didactic material. Suggestions and arguments made by different experts were taken into consideration, which were largely the basis for the realization of the work from the point of view of its methodological conception. The criteria offered by teachers and students once the album was implemented, in the teaching-learning process of Invertebrate Zoology in the academic year 2021, were also considered. The effectiveness of the developed teaching medium became evident, taking into consideration the results obtained by the students during the teaching-learning process of the subject. It is concluded that the topic addressed is important and coincides with the transformations that are taking place in the National Education System in Cuba in times of COVID-19.